ANNEALING KINETICS OF FISSION TRACKS IN ZIRCON: AN EXPERIMENTAL STUDY - Yamada R.; Tagami T.; Nishimura S.; Ito H. (My University, 1996)
A series of laboratory annealing experiments on zircon fission tracks has been carried out under heating conditions of 350–750°C for 10−1–103 hr (i.e. 4.5 min-∼40 days). Variation in the confined lengths of spontaneous fission tracks was determined using zircon grains from Nisatai Dacite. The fading contours of normalized mean track length (r) on the Arrhenius diagram showed as sets of straight lines. We performed a series of model fittings, called the parallel and fanning models, in order to describe the decrease in r with increasing temperature or heating time. The lowest temperature limit of the zircon partial annealing zone (ZPAZ) was defined as r ≈ 0.95, and the highest as r ≈ 0.4, which approximately corresponded to the total fading of surface tracks. Extrapolation of the results of the laboratory experiments to the geological timescale gives, for a heating duration of 106 yr, estimated values of the ZPAZ of ∼210–320°C (± 60°C, 2σ) with the parallel model; ∼190–350°C (± 50°C, 2τ) with the fanning model (critical temperature, T0 = ∞); and ∼170–390°C (±50°C, 2σ) with the fanning model (T0 ≠ ∞). The temperatures of the ZPAZ decrease by ∼20°C for an annealing duration that is an order of magnitude longer. Because the estimated closure temperature of zircon fission-track analysis approximately corresponds to the middle of the ZPAZ, these results support the previously estimated closure temperature of ∼240°C. By varying the etching time it was revealed that significant removal of α-radiation damage occurs at r ≈ 0.93.